2018
DOI: 10.5606/tftrd.2018.2246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insoles with arch support on gait pattern in patients with multiple sclerosis

Abstract: Objectives: This study aims to determine the effect of insoles with arch support on gait patterns in patients with multiple sclerosis (MS) and somatosensory impairment. Patients and methods: Ten patients (7 females, 3 males; mean age 34.9±6.8 years; range, 48 to 35 years) with clinically definite relapsing remitting MS and age-and sex-matched 10 healthy volunteers (7 females, 3 males; mean age 33.8±3.2; range, 40 to 31 years) were included in the study between January 2011 and January 2012. A medial longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Despite the high percentage of patients with biomechanical problems such as claw toes and clubfoot [5], we emphasize that no research on foot orthoses (custom-made or prefabricated) in PD patients has been found. However, the effectiveness of foot orthoses has been demonstrated for other neurodegenerative disorders [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high percentage of patients with biomechanical problems such as claw toes and clubfoot [5], we emphasize that no research on foot orthoses (custom-made or prefabricated) in PD patients has been found. However, the effectiveness of foot orthoses has been demonstrated for other neurodegenerative disorders [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff to select or reject a particular manuscript is 19; the manuscripts below this range will be rejected. As per the interpretation of Modified Downs and Black 27-point scale: excellent (26-28); good (20-25); fair (15)(16)(17)(18)(19); and poor (less than=14). This scale determines the quality of the content of literature on the basis of its parameters such as reporting, internal validity, external validity and power.…”
Section: Assessment Of (Risk Bias and Quality) Individual Studiesmentioning
confidence: 98%
“…Xu et al developed an algorithm based on compressed sensing with one accelerometer for accurate detection of human behavior [15]. Usage of insoles affects the gait parameters in patients with various neuromuscular disorders and has effect on preventing gait related abnormalities [16]. However, no research has been carried out on the use of smart sensor insole in improving walking among patients with lower limb arthroplasty.…”
Section: Introductionmentioning
confidence: 99%